Performance of Geopolymer Concrete Exposed to Freezing and Thawing Cycles - Mohammed Shamsa; Basil Al-Shathr; Tareq al-Attar (Engineering and Technology Journal, 2019)
In this study, the effect of rapid freezing and thawing (ASTM C666 – procedure A) on three different types of Geopolymer concrete studied using three types of pozzolanic material: fly ash, metakaolin and ground granulated blast furnace slag (GGBFS). The Geopolymer concrete was prepared using 400 kg of the pozzolanic material with alkaline liquid prepared at 8 molar concentration with normal fine and coarse aggregates. The ratio of alkaline to fly ash and GGBFS was 1.5: 1 and for metakaolin was 2: 1 for workability and compressive strength requirements. Specimens (100 × 100 × 400) mm were exposed to 100, 200 and 300 cycles of freezing and thawing. The decrease in measured compressive strength was (23, 43, and 26%) for Fly ash, metakaolin and GGBFS respectively. The investigated types of concrete showed good resistance to freezing and thawing. The durability factor of these types was (77%, 68%, and 81%) for fly ash, metakaolin, and GGBFS respectively.